THE CIVILIAN AND MILITARY COOPERATION IN MANAGING THE COVID-19 PANDEMIC AS PART OF MILITARY OPERATION OTHER THAN WAR : THE ACHIEVEMENT TOWARDS A RESILIENT WHOLE OF SOCIETY APPROACH IN MALAYSIA - Mohd Zaki Jusoh (Tesis, 2021)
The objective of this study is to determine the Civillian and Military Cooperation (CIMIC) concept in managing the national pandemic crisis towards the achievement of Malaysia's resilient Whole of Society Approach.